Factors affecting consumer attitude towards mobile advertising in India. (15th January 2010) - Mathew, Mary; Dambal, Anirudha
There has been a tremendous growth in the mobile telecommunication industry in India. India has already crossed the 250 million users mark in February 2008. At the same time, there has also been a growth in the mobile advertising space in India. Although several papers have been written in the recent times about consumer attitudes towards mobile advertising, a systematic study of these for India is lacking. This paper has tried to address this need. The study is aimed at understanding the attitudes towards mobile based advertisement and variables influencing it. After surveying the increasing body of recent literature on mobile advertising, the paper proposed a conceptual model. This model was empirically tested to find the factors contributing to a positive consumer attitude towards mobile advertising. The paper revealed that the overall attitudes towards mobile advertisement are not too high in the Indian sample. It concluded that the two factors affecting consumers' attitude towards mobile advertising are non-consumer centric factors and consumer centric factors. The study also showed that non-consumer centric variables namely technology and content of advertisements must be managed to create a positive attitude towards mobile based advertising in India.